Shock, Not Blood Pressure or Shock Index, Determines the Need for Thoracic Damage Control Following Penetrating Trauma. Issue 1 (July 2020) - Deane, Molly; Galvagno, Samuel M.; Moran, Benjamin; Stein, Deborah M.; Scalea, Thomas M.; O'Connor, James V.
ABSTRACT: Background: Damage control laparotomy has increased survival for critically injured patient with penetrating abdominal trauma. There has been a slower adoption of a damage control strategy for thoracic trauma despite the considerable mortality associated with emergent thoracotomy for patients in profound shock. We postulated admission physiology, not blood pressure or shock index, would identify patients who would benefit from thoracic damage control. Study Design: Retrospective trauma registry review from 2002 to 2017 at a busy, urban trauma center. Three hundred one patients with penetrating thoracic trauma operated on within 6 h of admission were identified. Of those 66 (21.9%) required thoracic damage control and comprise the study population. Results: Compared with the non-damage control group, the 66 damage control patients had significantly higher Injury Severity Score, chest Abbreviated Injury Scale, lactate and base deficit, and lower pH and temperature. In addition, the damage control thoracic surgery group had significantly more gunshot wounds, transfusions, concomitant laparotomies, vasoactive infusions, and shorter time to the operating room. Notably, however, there were no significant differences in admission systolic blood pressure or shock index between the groups. Once normal physiology was restored, chest closure was performed 1.7 (0.7) days after the index operation. Mortality for thoracic damage was 15.2%, significantly higher than the 4.3% in the non-damage control group. Over two-thirds of damage control deaths occurred prior to chest closure. Conclusions: Mortality in this series of severely injured, profoundly physiologically altered patients undergoing thoracic damage control is substantially lower than previously reported. Rather than relying on blood pressure and shock index, early recognition of shock identifies patients in whom thoracic damage control is beneficial.